The dynamics of infidelity : applying relationship science to psychotherapy practice - Josephs, Lawrence (American Psychological Association, 2018)
"In this groundbreaking book, Lawrence Josephs argues for a new understanding of the psychological foundations of "cheating." Relationships are complicated. And as many therapists know, infidelity is a distressingly common issue for romantic couples. Unfortunately, most psychotherapy approaches tend to see infidelity as a manifestation of broader underlying problems and rarely offer insights or interventions to specifically address unfaithfulness and the impulses behind it. Drawing on research in social, personality, and evolutionary psychology that examines the crucial roles of attachment theory and "dark" personality traits such as narcissism and low empathy, Josephs offers a complex but intuitive model that explains how and when intimate relationships work, and don't work. His integrative and compassionate approach to treatment is grounded in psychodynamic principles, yet uses interventions from a variety of approaches, including mentalization-based therapies, emotion-focused therapy, marital communication skills training, and mindfulness/acceptance techniques. This book is a thought-provoking read for individual, family, and couples therapists seeking insights on how to address infidelity in their practice."--Preface. (PsycINFO Database Record (c) 2017 APA, all rights reserved)